DIMENSI HIERARKI KEBUTUHAN TOKOH UTAMA DALAM KUMPULAN CERPEN “KUKILA” KARYA AAN MANSYUR: KAJIAN PSIKOLOGI HUMANISTIK - Mega Adriyanti; Annisa Pramudita Kumala; Hendry Sugara (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to analyze the hierarchy of needs through the main characters of the six short stories contained in the short stories anthology “Kukila” by Aan Mansyur. The researcher limited the research to six selected short stories, “Kebun Kelapa di Kepalaku”, “Setia Adalah Pekerjaan yang Baik”, “Ketinggalan Pesawat”, “Celana Dalam Rahasia Terbuat Dari Besi”, “Tiba- Tiba Aku Florentino Ariza” and “Aku Selalu Bangun Lebih Pagi”. The analysis of the hierarchy of needs of the main characters from the six short stories was studied using humanistic psychology theory, namely the hierarchy of needs initiated by Abraham Maslow. This research method uses an analytical description method with a qualitative approach to reveal the dimensions of the hierarchy of needs in the short stories. The six short stories contain five concepts of the hierarchy of needs found, including; (1) physiological needs, (2) safety needs, (3) love and belonging needs, (4) self-esteem needs, and (5) self-actualization.